Digital and informatics competencies: Requirements for nursing leaders in Canada. Issue 6 (November 2021) - Lo, Brian; Nagle, Lynn M.; White, Peggy; Kleib, Manal; Kennedy, Margaret Ann; Strudwick, Gillian
The use of health information technologies continues to grow, especially with the increase in virtual care in response to COVID-19. As the largest health professional group in Canada, nurses are key stakeholders and their active engagement is essential for the meaningful adoption and use of digital health technologies to support patient care. Nurse leaders in particular are uniquely positioned to inform key technology decisions; therefore, enhancing their informatics capacity is paramount to the success of digital health initiatives and investments. The purpose of this commentary is to reflect on current projects relevant to the development of informatics competencies for nurse leaders in the Canadian context and offer our perspectives on ways to enhance current and future nurse leaders' readiness for participation in digital health initiatives. Addressing the digital health knowledge and abilities of nurse leaders will improve their capacity to champion and lead transformative health system changes through digital innovation.